Geology and Wine 10: Use of Geographic Information System Technology to Assess Viticulture Performance in the Okanagan and Similkameen Valleys, British Columbia - Bowen, P.; Bogdanoff, C.; Estergaard, B.; Marsh, S.; Usher, K.; Smith, C.; Frank, G. (Geoscience Canada, 2005)
SUMMARY The complex geological history of the Okanagan and Similkameen valleys in British Columbia has created a wine growing region by way of diverse bedrock, soils, terrain and climate. Although wine grapes have been grown in the area for many decades, a recent conversion of vineyards to predominately Vitis vinifera varieties, and the subsequent world recognition of wine quality, suggests that there is further potential to improve wine quality through fine-tuning of grape varietal choices and vineyard management techniques. A geographic information system (GIS) application has been developed to study the relationships among site conditions, management practices and vineyard performance including fruit and wine quality. The production area was divided into six regions based on landform and climate: 1. Kelowna, 2. Penticton, 3. Vaseaux - Oliver, 4. Golden Mile, 5. Black Sage - Osoyoos, and 6. Similkameen. The complement of grape varieties planted varies among the regions. Comparisons of regional patterns of varieties planted, and medals received, have revealed significant regional differences in varietal suitability. Although most of the vineyards are sited on coarse-textured soils, comparisons of the distributions of all and medal-winning vineyard blocks among soil textural classes have revealed that quality wine grapes are grown on a broad range of soil types within, and among, the six regions studied. Loamy soils appear to be especially suitable for producing quality wine grapes in the Okanagan and Similkameen valleys.